Rancang Bangun Sistem Informasi Penentu Calon Penerima Beasiswa pada Fakultas Ekonomi Universitas Garut - Ridwan Setiawan; Ayu Latifah; Wulan Dwi Lestari; Andri Ikhwana (Institut Teknologi Garut, 2022)
Garut University is a private tertiary institution in Garut which was established in 1998. The Faculty of Economics (Faculty of Economics) is one of the faculties at Garut University. The process of distributing scholarships in this faculty is still done manually by sending files to student affairs directly and repeatedly. . The purpose of this study is to design a determinant of prospective scholarship recipients which can assist in the process of distributing scholarships quickly, precisely and accurately. The methodology used in software engineering is the Rational Unified Process (RUP) methodology with the stages used inception, elaboration, and construction, with the modeling used the Unified Modeling Language (UML) with use case diagrams, activity diagrams, sequence diagrams and class diagrams. In the Rational Unified Process methodology, the stages are limited to construction, while the transition phase is not carried out. The results of this study are the design of a web-based information system for determining prospective scholarship recipients.